Serum Selenoprotein P level is not indicative of Insulin Resistance in Children and Adolescents with Type 1 Diabetes Mellitus: Single Center Experience - Hend Mehawed Soliman; Balsam Sherif Fahmy; Selim Mohamed Abdelkader; Samah A. Hassanein (Pediatric Sciences Journal, 2022)
Background: Selenium has an anti-diabetic action as it an insulin-mimetic and antioxidant nutrient. Selenoprotein P (SeP) is an extracellular glycoprotein, that was linked to insulin resistance (IR). Aim: To validate of serum SeP as a measure for insulin resistance in patients with type 1 diabetes mellitus (T1DM). Methods: This prospective case-control study included 45 children and adolescents with T1DM and 45 healthy children and adolescents. Serum SeP was measured by ELISA and compared to estimated glucose disposal rate (eGDR) as a measure of insulin resistance. Results: Mean ± SD of SeP level was higher in T1DM patients than control group (59.78 ± 59.38 ng/ml, 55.57 ± 7.6 ng/ml,respectively), this difference was statistically insignificant (p= 0.642). SeP demonstrated significant positive correlations with duration of diabetes (r=0.413, p=0.005), high density lipoproteins (r=0.496, p=0.001) and glycosylated hemoglobin (r=0.357, p=0.016). There were statistically significant differences in eGDR between cases and controls (7.78±3.08 mg/kg/min, 12.53±0.91mg/kg/min, respectively, (p= 0.001). There was no correlation between SeP level and eGDR values (IR indicator). Conclusion: Serum SeP level in T1DM patients was not indicative of IR. Higher serum SeP level are associated with longer duration and poor control of T1DM.